On the mean square displacement of a random walk on a graph. (January 2016) - Im, Seonghyuk; Kim, Hwidong; Maeng, Jiho; Yu, Jihwan; Cha, Yongwook; Paeng, Seong-Hun
Abstract: We study a relation between Ollivier's Ricci curvature and the mean square displacement of a random walk on a graph. Also we obtain explicit formulas for the mean square displacement of random walks on regular polyhedra.